Taxonomic notes on some species of genus Charopus Erichson, 1840 in the Mediterranean Region (Coleoptera: Cleroidea, Melyridae, Malachiinae) - Franzini, Gabriele (Fragmenta entomologica, 2022)
The results of the study of several hundred specimens of the genus Charopus, preserved in public and private collections from the Mediterranean region are here presented. For C. rotundatus Erichson, 1840 the neotype is here described. C. nitidus Küster, 1849 stat. rest. and C. multicaudis Kiesenwetter, 1866 stat. rest. are resurrected from synonymy with C. rotundatus and regarded as valid species. For C. nitidus Küster, 1849 stat. rest. a neotype is designated and described. Charopus varipes Baudi di Selve, 1872 stat. rest. is resurrected from synonymy with C. pallipes (A.G. Olivier, 1790) and regarded as a valid species. Elements for identification of the above mentioned species are provided in the form of comparative tables, and distributional data; list of known localities are also supplied. The distributions of Charopus apicalis Kiesenwetter, 1859, C. concolor (Fabricius, 1801) and C. flavipes (Paykull, 1798) are also briefly discussed. The new synonymy Cyrtosus (Oogynes) reitteri Abeille de Perrin, 1890 = Charopus crassicornis Wittmer, 1975 is proposed. A partial key to known males of Western Palaearctic species is also provided.